The Electrochemical Performances of n-Type Extended Lattice Spaced Si Negative Electrodes for Lithium-Ion Batteries - Lee, Moonsang; Yoon, Dockyoung; Lee, Uk Jae; Umirov, Nurzhan; Mukanova, Aliya; Bakenov, Zhumabay; Kim, Sung-Soo (Frontiers in Chemistry, 2019)
The electrochemical performances of lithium-ion batteries with different lattice-spacing Si negative electrodes were investigated. To achieve a homogeneous distribution of impurities in the Si anodes, single crystalline Si wafers with As-dopant were ball-milled to form irregular and agglomerated micro-flakes with an average size of ~10 µm. The structural analysis proved that the As-doped Si negative materials retain the increased lattice constant, thus, keep the existence of the residual tensile stress of around 1.7 GPa compared with undoped Si anode. Electrochemical characterization showed that the As-doped Si anodes have lower discharge capacity, but Coulombic efficiency and capacity retention were improved in contrast with those of the undoped one. This improvement of electrochemical characteristics was attributed to the increased potential barrier on the side of Si anodes, inherited from the electronic and mechanical nature of Si materials doped with As. We believe that this study will guide us the way to optimize the electrochemical performances of LIBs with Si-based anodes.